National Early Warning Score 2 Lactate (NEWS2-L) in Predicting Early Clinical Deterioration in Patients with Dyspnoea in Prehospital Care - Villanueva Rábano, Raúl; Martín-Rodríguez, Francisco; López-Izquierdo, Raúl (Investigación y Educación en Enfermería, 2021)
Objective. To evaluate the ability of the NEWS2-L (National Early Warning Score 2 Lactate) scale to predict the risk of early clinical deterioration (mortality within 48 hours) in patients with dyspnoea treated by the Medical Emergency Services compared with NEWS2 and lactate in isolation. Methods. Prospective, multi-centre study of a cohort of 638 patients with dyspnoea treated in the ambulance and priority-transferred to a hospital emergency service in the cities of Valladolid, Salamanca, Segovia or Burgos (Spain). We collected clinical, analytical and demographic data. The main outcome measure was all-cause mortality within 48 hours. The recommendations of the Royal College of Physicians were followed to calculate NEWS2. When NEWS2 and LA prehospital values were obtained, the two values were added together to obtain the NEWS2-L. Results. Mortality within 48 hours was fifty-six patients (8.8%). The NEWS2-L scale obtained an area under the curve (AUC) of the receiver operating characteristics (ROC) for mortality within 48 hours of 0.854 (CI 95% 0.790–0.917), at seven days of 0.788 (CI 95% 0.729–0.848) and at 30 days of 0.744 (CI 95% 0.692–0.796); in all cases p<0.001, with a significant decrease between the value at 48 hours and at 30 days. Conclusion. The NEWS2-L scale was found to be significantly superior to the NEWS2 scale and similar to lactate in predicting early clinical deterioration in patients with dyspnoea. This scale can help a nurse detect these patients early, as part of their regular practice, and thus guide therapeutic efforts.